Feeding activity of the corallivorous gastropod Quoyula monodonta (Blainville) - Guzmán, Héctor M. (Revista de Biología Tropical, 1988)
The predatory behavior of the gastropod Quoyula monodonta, a selective corallivore that feeds upon Pocillopora spp., is reported for the first time from the eastern Pacific. On average an individual eats tissue from 0.64 cm2 of coral per day. Larger individuals cause more damage. The high densities of Q. monodonta and two species of hermit crab, make it likely that all of these corallivores are acting together to increase the mortality of pocilloporid corals and thus limit the growth, abundance and distribution of Pocillopora on the Caño Island coral reefs (Costa Rica).